OPTIMALISASI PERAN ANALISA STAN DAR BELANJA DALAM PENYUSUNAN ANGGRAN BELANJA SKPD DI KABUPATEN LINGGA - Alek Murtin (Jurnal Riset Akuntansi dan Bisnis)
The purpose of this study provides a reasonable budgetary level in each SKPD in Lingga District, which can be used as guidance in preparing the budget in the coming year. The contribution of this research to local government can be used as predictor of fairness of expenditure of each SKPD and as a control tool for Local Government Budget Team (TAPD) at the time of discussion of Work Plan Budget (RKA) in the coming year. Approach in this research use perspective of science management accounting, cost accounting and statistics sciences. This research is descriptive research, in data analysis using Activity Based Costing (ABC) method and Ordinary Least Square (OLS) data processing using SPSS with descriptive statistical technique.